2020
DOI: 10.1007/s42979-020-00275-z
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular Perception Based on Inertial Sensing: A Structured Mapping of Approaches and Methods

Abstract: In this paper, we present a structured literature mapping of the state-of-the-art of vehicular perception methods and approaches using inertial sensors. An in-depth investigation and classification were performed employing the results of a systematic literature review. The analysis focused on identifying methods that capture signals provided by inertial sensors such as accelerometers and gyroscopes to recognize transient or persistent events associated with the vehicle's movement. We classified these events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(214 reference statements)
0
8
0
Order By: Relevance
“…We decided to place the sensor on the top of car’s dashboard in the middle of the car, because it is a common placement position for the IMU in the literature [ 12 ]. In the recent review by Menegazzo et al [ 4 ], the placement of the IMU on the top of car’s dashboard was the one mostly adopted in the literature. The results from [ 8 ] also showed that the placement on the dashboard provided the smallest classification error in comparison to the placement of the IMU in other locations on the vehicles (e.g., left or right side of the car).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We decided to place the sensor on the top of car’s dashboard in the middle of the car, because it is a common placement position for the IMU in the literature [ 12 ]. In the recent review by Menegazzo et al [ 4 ], the placement of the IMU on the top of car’s dashboard was the one mostly adopted in the literature. The results from [ 8 ] also showed that the placement on the dashboard provided the smallest classification error in comparison to the placement of the IMU in other locations on the vehicles (e.g., left or right side of the car).…”
Section: Methodsmentioning
confidence: 99%
“…The data collection was performed using the controlled positioning strategy. As described in [ 4 ], this strategy consists of a simple technique where the sensor is placed on the vehicle so that the axes in both reference frames coincide, i.e., the sensor axes are aligned with the vehicle axes, and it is not necessary to apply preprocessing for reorientation. This technique was used for both accelerometer and gyroscope data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations